PERANCANGAN LOWONGAN KERJA ONLINE BERBASIS WEB PADA PT ANH - Akhsani Taqwiym; Novan Wijaya (Jurnal Ilmiah Informatika, 2017)
Internet technology is currently growing, as well as the flow of communication in the delivery of employment information provided or required by various parties, including government and private. Before the existence of information technology, job vacancy still use conventional method that is by installing announcement on office walls and print media. Along with the development of information technology, job apangan provided at this time, informed very quickly and have many advantages such as job seekers only open information about job vacancy through websites that have been available. But in the delivery of job vacancy has a constraint that there are parties who have bad intentions by spreading vacancies that are not actually there. So it hurts job seekers, whether material or time. Currently, job seekers do not need to come directly to companies that need jobs but can directly send the application via E-mail. To reduce the act of fraud committed by irresponsible person then needed a system that help job seekers get good information and correct. Therefore, the alternative of the solution is to use a web-based information technology system so that job seekers can directly see and communicate with companies that open job vacancies. In the design of a software system contains job vacancy information and job seeker data processing. The designed software is still a prototype, using Data Flow Diagrams (DFD) and Entity Relationship Diagram (ERD).